The Value of MicroRNA-375 Detection for Triaging Primary Human Papillomavirus Positive Women: A Cross-Sectional Study in a General Population - Wu, Qiongyan; Wang, Lingfang; Zhao, Xiumin; Tian, Qifang; Wang, Fenfen; Sima, Ni; Qiu, Liqian; Lu, Weiguo; Xie, Xing; Wang, Xinyu; Cheng, Xiaodong (Frontiers in Oncology, 2021)
Purpose: To validate the value of microRNA (miRNA) detection for triaging human papillomavirus(HPV)-positive women in the general population. Patients and methods: MiR-375 detection in cervical exfoliated cells has been demonstrated to have the superior value to cytology in triaging primary HPV-positive women in the hospital population. In this study, residual samples of cervical exfoliated cells from 10,951 women in a general population were used to detect miRNA. The performance efficiency of miRNA detection in identifying high-grade cervical intraepithelial neoplasia (CIN) was evaluated. Pearson chi-square test and McNemar pairing test were used to compare miRNA detection and cytology. Results: In valid 9,972 women aged 25-65, miR-375 expression showed a downward trend along with an increase in cervical lesion severity. The expression level of miR-375 ≤ 1.0 × 10-3 was identified as positive. In the HPV-positive and 12 HPV genotypes other than 16/18 (HR12)-positive women, miR-375 detection showed equivalent sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) to that of cytology (≥ ASC-US), higher or similar sensitivity and NPV, but lower specificity and PPV than that of cytology(≥ ASC-H) in identifying CIN3+ and CIN2+. In HPV 16-positive women, miR-375 positivity had higher sensitivity and NPV, but lower specificity and PPV than that of cytology (≥ ASC-H and HSIL) in identifying CIN3+ and CIN2+. The immediate CIN3+ risk of miR-375 positivity was 19.8% (61/308) in HPV-positive, 10.8% (22/204) in HR12-positive, and 43.5% (37/85) in HPV16-positive women, respectively. Conclusion: The detection of miR-375 in cervical exfoliated cells may be an optional method for triaging primary HPV-positive women in population-based cervical cancer screening.